Natural Language Processing: Semantic Aspects - Kapetanios, Epaminondas; Tatar, Doina; Sacarea, Christian (CRC Press, 2013)
This book introduces the semantic aspects of natural language processing and its applications. Topics covered include: measuring word meaning similarity, multi-lingual querying, and parametric theory, named entity recognition, semantics, query language, and the nature of language. The book also emphasizes the portions of mathematics needed to under